Analisis Pemahaman Mahasiswa Kedokteran Umgo Gorontalo 2023 Terhadap Laboratorium Praktikum Anatomi - A Muh Rifqi Ismulail (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
One infrastructure facility that supports understanding the medical science education process is the anatomy laboratory. The role of the laboratory is to provide practical experience for students to understand the structure of the human body. This research aims to measure the understanding of medical students at Muhammadiyah University of Gorontalo regarding the anatomy laboratory and identify the factors that influence it. The method used in this research is a qualitative method with a phenomenological approach. This approach aims to understand the subjective experiences and perceptions of UMGO medical students regarding the anatomy practicum laboratory. The results obtained indicate that students' knowledge of the anatomy laboratory practicum is quite good. Regarding the most difficult material in the anatomy practicum, the majority of students identified the nervous system as the most challenging. The conclusion is that medical students at the Muhammadiyah University of Gorontalo are expected to have the ability to understand anatomy lessons, which requires improving learning methods and intensive assistance from laboratory assistants.